The Macanese diaspora in British Hong Kong : a century of transimperial drifting - Chan, Catherine S. (Asian history., 2021)
Diaspora transformed the urban terrain of colonial societies, creating polyglot worlds out of neighborhoods, workplaces, recreational clubs and public spheres. It was within these spaces that communities reimagined and reshaped their public identities vis-à-vis emerging government policies and perceptions from other communities. Through a century of Macanese activities in British Hong Kong, this book explores how mixed-race diasporic communities survived within unequal, racialized and biased systems beyond the colonizer-colonized dichotomy. Originating from Portuguese Macau yet living outside the control of the empire, the Macanese freely associated with more than one identity and pledged allegiance to multiple communal, political and civic affiliations. They drew on colorful imaginations of the Portuguese and British empires in responding to a spectrum of changes encompassing Macau?s woes, Hong Kong?s injustice, Portugal?s political transitions, global developments in print culture and the rise of new nationalisms during the inter-war period.